1993
DOI: 10.1002/pd.1970130503
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin gene analysis and prenatal diagnosis of Duchenne muscular dystrophy in Russia

Abstract: Of 126 families referred for counselling of Duchenne muscular dystrophy (DMD), DNA analysis has been suggested to 119 families with at least one affected child or with an affected close male relative of the woman at risk of being a DMD carrier. A large proportion (about 80 per cent) of the families were represented by sporadic cases (only one affected individual). By means of multiplex polymerase chain reactions with different sets of oligoprimers providing amplification of 10-11 different exons, altogether 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…the Egyptian genetic background of DMD and BMD. The analysis involved 18 exons that were known to be clustered in the minor hot spot (exons Pm1, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; that partially covers the NH2 terminal region and the rod domain; and the major hot spot (exons 43-60), respectively [10,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the Egyptian genetic background of DMD and BMD. The analysis involved 18 exons that were known to be clustered in the minor hot spot (exons Pm1, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; that partially covers the NH2 terminal region and the rod domain; and the major hot spot (exons 43-60), respectively [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…Each reaction produces three separable bands visualized on a 3% agarose ethidium stained gel. Exons studied were: Pm1, 3…”
Section: Methodsmentioning
confidence: 99%
“…Russian [Baranov et al, 1993] and Czechoslovakian [Kádasi et al, 1991] patients also showed a much lower percentage of deletions (41% and 44%, respectively) than that from other European countries [Den Dunnen et al, 1989;Niemann-Seyde et al, 1992;Covone et al, 1992]. Baranov et al [1993] reported deletion studies in two groups of patients. In Saint Petersburg, 11 exons were examined, while in Moscow only 10 exons were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Most mutations in the DMD gene are intragenic deletions (65%) or duplications (5%) [Koenig et al, 1988;Forrest et al, 1988;Hu et al, 1988]. A number of studies have documented the frequency and distribution of deletions in different parts of the world [Den Dunnen et al, 1989;Gillard et al, 1989;Chamberlain et al, 1992;Covone et al, 1992;Imoto et al, 1993], and some authors have suggested that these vary with ethnic origin [Sugino et al, 1989;Tsukamoto et al, 1991;Kádasi et al, 1991;Baranov et al, 1993;Ballo et al, 1994]. There have so far been only two small studies of exonal deletions among patients with DMD in India [Sinha et al, 1992;Saxena and Verma, unpublished results].…”
Section: Introductionmentioning
confidence: 99%
“…In American studies, mutant alleles with gene deletions have been reported in 55-70% of all DMD/ BMD cases (Koenig et al 1987;Liechti-Gallati et al 1989), but the proportion is significantly lower, particularly in some Asian and European patients (Soong et al 1991;Baranov et al 1993;Gokgoz et al 1993;Florentin et al 1994;Patino et al 1995). Moreover, subtle differences in distribution of breakpoints have also been reported, even within European populations (Danieli et al 1993).…”
Section: Introductionmentioning
confidence: 99%